Analysing intersections between climate change and human rights - Daniel Uribe Terán; Luis Fernando Rosales (South Centre, 2022)
The effects of climate change on people's daily lives threaten the full enjoyment of human rights. The Human Rights Council adopted two landmark resolutions recognising the human right to a clean, healthy and sustainable environment (Resolution 48/13), and establishing the mandate for a Special Rapporteur on the promotion and protection of human rights in the context of climate change (Resolution 48/14). Nevertheless, a broader dialogue between the UNFCCC and the UN human rights architecture seems necessary to establish a coordinated and coherent response to climate change and its effects on human rights. This research paper analyses the intersections of these two legal systems. It does so by identifying how the climate change negotiations and the human rights architecture can contribute to strengthening international cooperation. It also recognises the need for a more profound international debate on the linkages between human rights and climate change consistent with the principles of equity and common but differentiated responsibilities included in the UNFCCC.
Keywords: 300; Adaptation; Business and Human Rights; Capacity Building; Climate Action; Climate Change; Climate Finance; Common But Differentiated Responsibility (CBDR); Conferences of the Parties (COP); COP26; Equity; Human Rights; Human Rights Council; Human Rights Due Diligence (HRDD); Intergovernmental Panel on Climate Change (IPCC); International Investment Agreements (IIAs); Investment; Investor-State Dispute Settlement (ISDS) System; Just Transition; Loss and Damage; Mitigation; Paris Agreement; Reform of the IIA regime; Right to a Clean and Safe Environment; Technology Transfer; United Nations Framework Convention on Climate Change (UNFCCC)